Numerical computation for dual stratification of slip flow of sutterby nanofluids with heat generation features - Ullah, Ubaid; Shah, Syed Inayat Ali; Nisar, Kottakkaran Sooppy; Khan, Hamid; Ullah, Naeem; Yousaf, Muhammad (Frontiers in Materials, 2023)
The current communication, manifest mathematical modelling and numerical computations of sutterby nanofluids with radiant heat assessment subject to heat generation/absorption. The thermophoresis and Brownian motion effects are incorporated via Buongiorno model in flow governing equations. Moreover, the present analysis manifest the impacts of thermal stratification, velocity slip and magnetic field on flow phenomena. The non-Newtonian nature is modelled using sutterby fluid. The proposed model is formulated mathematically through basic partial differential equations relating mass, momentum, energy and nanoparticles concentration conservations using boundary layer theory. We adapted the generated governed equations to ordinary differential equations utilizing similarity variables mechanism. Numerical treatment for the reduced system of ordinary differential equations is performed using built-in MATLAB code, bvp4c. The impacts of distinct characterizing parameters on velocity, temperature and concentration profiles are determined and analyzed via graphs. The existence of velocity slip parameter, fluid flow is significantly dwindle, while the surface friction growth is sophisticated. Brownian and thermophoresis mechanism degrade the heat transmission rate and escalates the mass flux. The thermal and solutal stratification exhibits opposite conduct for thermal and concentration of the nanoparticles.